The Effectiveness of Gadget-Based Interactive Multimedia in Improving Generation Z’s Scientific Literacy - Widodo, W.; Sudibyo, E.; Suryanti, S.; Sari, D. A. P.; Inzanah, I.; Setiawan, B. (Jurnal Pendidikan IPA Indonesia, 2020)
Scientific literacy is very important to generation Z (Gen-Z), while Gen-zÃ¢â‚¬â„¢s scientific literacy in Indonesia needs to be improved. The use of gadgets by Gen-Z almost all the time in their daily lives enables research to improve scientific literacy by using gadgets. This study aims to determine the effectiveness of gadget-based interactive multimedia to improve Gen-Z scientific literacy and describe the Gen-Z response to interactive multimedia. This research was a pre-experiment study with one group pretest and posttest design. Interactive multimedia was designed to be applied on gadget, consists of Socioscientific Issues (SSI) which was relevant to pressure concepts. This research involved two junior high schools in East Java, Indonesia. Scientific literacy test instrument was designed based on scientific literacy aspects of PISA 2015. The inferential test results showed that posttest score was significantly greater than the pretest in the two schools. Results showed that the mean score of studentsÃ¢â‚¬â„¢ scientific literacy at School I increased from 39.6 to 74.0 and N-gain score was 0.57 which was in medium category. In addition, the average scientific literacy score of students in School II also increased from 31.5 to 59.9 and Ngain score was 0.41 which was in the medium category. The inferential test results also showed that there were no significant N-gain differences in the two schools. It can be concluded that interactive multimedia developed effective to improve studentsÃ¢â‚¬â„¢ scientific literacy. However, Gen-Z students cannot be satisfied with the multimedia. Students suggest several multimedia enhancements in terms of visual, audio, and music, so that they can enjoy the multimedia all the time by using the device.Ã‚Â